Sexual assault among North Carolina women: prevalence and health risk factors. Issue 4 (1st April 2002) - Cloutier, S; Martin, S L; Poole, C
Abstract : Study objective: Sexual assault is traumatic at the time it occurs, but it also may have longlasting negative effects on physical health. Much of the research linking specific health problems to sexual assault victimisation has used samples from special populations. The goals of this study are to estimate the prevalence of sexual assault in a representative sample of women in North Carolina and examine sexual assault in relation to specific health risk factors for leading causes of morbidity and mortality in women. Design: The North Carolina Behavioral Risk Factor Surveillance System (BRFSS) is a household telephone survey of non-institutionalised adults, 18 years of age and older, conducted by random digit dialling. Setting: This investigation focuses on the study participants in the 1997 survey. Participants: The sample includes 2109 women who responded to the sexual assault questions in the 1997 North Carolina BRFSS interview. Main results: The lifetime prevalence of sexual assault was 19% (95% CI 17% to 20%), of which 73% of victims experienced or were threatened with forced sexual intercourse. Sexual assault victims, particularly victims of forced intercourse or the threat thereof, were more likely to perceive their general health as being fair or poor (OR=2.3, 95% CI 1.5 to 3.4) and were more likely to have suffered poor physical and mental health in the past month (poor physical health, OR=2.1, 95% CI 1.6 to 2.8; poor mental health, OR= 2.6, 95% CI 1.9 to 3.5). After controlling for sociodemographic factors and health care coverage, victims of forced intercourse or the threat thereof were more likely to smoke cigarettes (OR=2.0, 95% CI 1.4 to 2.8), to have hypertension (OR=1.5, 95% CI 1.1 to 2.2), to have high cholesterol (OR=1.7, 95% CI 1.2 to 2.5), and to be obese (OR=1.7, 95% CI 1.3 to 2.4). Conclusions: This study shows associations between sexual victimisation and health risk factors in a non-clinical statewide population of women. Future research should determine whether clinically screening for and identifying a history of sexual victimisation among women seen in a variety of health care settings leads to the initiation of effective interventions that help women successfully cope with these violent experiences. There is also a need for further research to investigate the temporal sequence of assaults and subsequent health outcomes by assessing physical health status before and after victimisation.